In a nutshell focuses on the 1994 GATT/WTO Agriculture Agreement and other agreement of the Uruguay Round which are of relevance to global agricultural trade - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
20 páginas